2008
DOI: 10.1101/sqb.2008.73.033
|View full text |Cite
|
Sign up to set email alerts
|

Brief History, Pitfalls, and Prospects of Mammalian Spermatogonial Stem Cell Research

Abstract: Spermatogonial stem cells (SSCs) provide the foundation for spermatogenesis. During the last decade, several techniques for the manipulation of this cell type have been developed; as a result, SSCs can now be subjected to long-term in vitro expansion and genetically manipulated for knockout mouse production. These techniques have allowed SSCs to serve as a new target for animal transgenesis, which may provide an alternative to embryonic stem (ES) cells. Furthermore, SSCs may be converted into ES-like cells, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…SSCs are a special type among stem cells, and they can transmit genetic information to the next generation[6]. Kossack et al [7] suggested the potential to derive pluripotent cells from human testis biopsies but indicated a need for novel strategies to optimize human multipotent germline stem cells (hMGSCs) culture conditions and reprogram.…”
Section: Discussionmentioning
confidence: 99%
“…SSCs are a special type among stem cells, and they can transmit genetic information to the next generation[6]. Kossack et al [7] suggested the potential to derive pluripotent cells from human testis biopsies but indicated a need for novel strategies to optimize human multipotent germline stem cells (hMGSCs) culture conditions and reprogram.…”
Section: Discussionmentioning
confidence: 99%
“…Color images available online at www.liebertonline.com/scd chromosomal aberrations associated with the process of aging. Success has already been achieved to derive, propagate, and long term culture ES cells-like colonies without any genetic manipulation, from adult testicular tissue [48,49]. Transplantation of expanded bone marrow VSELs improved symptoms of myocardial infarct in mice [43].…”
Section: Putative Stem Cells In Mammalian Ovarymentioning
confidence: 99%
“…Thus, their small numbers and the lack of specific markers are the main hurdles to their characterization. Nonetheless, significant progress has recently been made in the isolation and propagation of cells with SSCs properties from rodent Guan et al 2009;Kanatsu-Shinohara, Takehashi, and Shinohara 2008;Kubota, Avarbock, and Brinster 2004;Brinster 2006, 2008;Ogawa et al 2003;Hofmann et al 2005;Kanatsu-Shinohara et al 2010) and human testes (Conrad et al 2008;Glaser et al 2008;Golestaneh et al 2009;Kossack et al 2009;Zovoilis et al 2008;Izadyar et al 2011;He et al 2009). Human testicular tissue is currently obtained from testicular biopsies (Izadyar et al 2011;Kossack et al 2009), orchiectomies (Izadyar et al 2011) and organ donors ).…”
Section: Current Methods Of Isolation and Propagation Of Sscs With Emmentioning
confidence: 99%